A novel self-alignment method for SINS based on three vectors of gravitational apparent motion in inertial frame. (February 2015) - Liu, Xixiang; Liu, Xianjun; Song, Qing; Yang, Yan; Liu, Yiting; Wang, Lihui
Highlights: The detail for SINS alignment based on gravitational apparent motion is given. The detail for latitude calculation based on gravitational apparent motion is given. The validity of the proposed method is proved by mathematical proof. The theoretical accuracies of alignment and latitude are deduced. Simulation and turntable test verified the validity of the proposed method. Abstract: Based on the alignment idea of tracing gravitational apparent motion in inertial frame, a novel self-alignment and latitude calculation method for Strapdown Inertial Navigation System (SINS) is designed. In this method, the problem of acquiring attitude matrix between body frame and navigation frame is attributed to acquiring the matrix between initial body frame and current navigation frame, and the gravitational apparent motion vectors at three moments are used to construct corresponding vectors and matrix through vector-operation. Meanwhile, the latitude information can be obtained by virtue of the geometric relationships among gravitational apparent vectors. Furthermore, the validity of the proposed method is proved by mathematical proof, and the theoretical expressions for evaluating accuracies of initial alignment and latitude calculation are deduced detailedly. Simulation and turntable results indicate that the proposed method can fulfill self-alignment and latitude calculation under a swinging condition without translational motion.